Caracterização microbiológica do veneno do ferrão do Bagre (Cathorops agassizii and Genidens genidens) - Junqueira, Marcos Emerson Pinheiro [UNESP]; Mondin, Alice Cristina; Lopes, Carlos Alberto de Magalhães [UNESP] (My University, 2006)
This work aimed to study the bacterial contamination of the catfishes stings Genidens genidens (Valenciennes, 1839); and Cathorops agassizii (Agassiz, 1829) found in the estuary-bay complex of Santos and São Vicente (São Paulo State). Fish samples for bacteriological analyses were obtained and constituted of a group of 50 specimens, being 25 of Cathorops agassizii and 25 of Genidens genidens,. The bacteriological analyses showed that there was contamination of the stings by 13 different strains of Enterobacteriaceae with Klebsiella pneumoniae (26,80%) as the most frequent bacteria and lower percentual frequencies for Enterobacter sp and Escherichia coli (16,27%) and Serratia marcescens, Serratia sp. and Proteus mirabilis (1,16%). Gram positive bacteria, as well fungi species were not detected in the samples. In basis of the Gram negative species characterized, is possible to consider the bacterial strains are representative of the environmental public health conditions, as well as, accidents with these fish stings are able to develop significative acute secondary infections in humans.
Microbiota characterization of the catfish (Cathorops agassizii and Genidens genidens) sting venom
Keywords: Accident; Brazilian catfishes; Microbiota; Secondary infection; Bacteria (microorganisms); Cathorops; Enterobacter; Enterobacteriaceae; Escherichia coli; Fungi; Genidens genidens; Hexapoda; Klebsiella pneumoniae; Negibacteria; Posibacteria; Proteus mirabilis; Serratia; Serratia marcescens; Serratia sp.; Siluriformes